2014
DOI: 10.1021/jp5016774
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Nonreactive Scattering of N2 off W(100): On the Influence of the Scattering Azimuth on In-Plane Angular Distributions

Abstract: The nonreactive scattering dynamics of N 2 off W(100) is theoretically investigated by means of quasi-classical trajectory simulations making use of a density functional theory-based potential energy surface. Over a wide range of collision energies, the evolution of the in-plane angular distributions, in agreement with experiment, can be interpreted in terms of direct scattering on the adiabatic potential energy surface. The results suggest that the evolution of the width of the angular distributions, which is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…for the hollow-parallel configuration, see Tables 4 and 5), are also reported in Table 8. [21], who looked at the non-reactive scattering of N 2 from a different tungsten surface (W(100)) and included dissipation to phonons using the GLO method.…”
Section: Energy Transfer To the Latticementioning
confidence: 99%
See 2 more Smart Citations
“…for the hollow-parallel configuration, see Tables 4 and 5), are also reported in Table 8. [21], who looked at the non-reactive scattering of N 2 from a different tungsten surface (W(100)) and included dissipation to phonons using the GLO method.…”
Section: Energy Transfer To the Latticementioning
confidence: 99%
“…Tungsten surfaces, among others, have received much attention [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21], with particular focus on the large crystallographic anisotropy that this metal exhibits with respect to nitrogen adsorption. For instance, the thermal reactivity of W(100) is about two orders of magnitude larger than the W(110) reactivity [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At relatively low surface temperature and thermal energies of the beam, the sticking coefficient is roughly S ≈ 1 on W(100). [8][9][10] However, the dissociation probability is decreased by two orders of magnitude on W(110) for the same range of surface temperature and kinetic energies. 11,12 The variation 2 in the reactivity between the two tungsten faces is due to the contribution of dynamical effects at distances relatively far from the surface and not to specific features of the surface active sites in which the atoms are eventually adsorbed after dissociation.…”
Section: Introductionmentioning
confidence: 95%
“…They showed that hydrogen prefers the TF position, in good agreement with other works based on DFT 20,21 . The penetration of hydrogen into the bulk via the W(100) 19,20,21 and W(110) 20,21,23,24 surfaces was also investigated by DFT, while the dissociation of molecular hydrogen was calculated via Molecular Dynamics (MD) calculations either based on DFT 25 or on model potentials 26,27 . However, in all cases, these works were conducted on a clean W surface, hence modeling a very low coverage; this is in contrast with real experimental conditions.…”
Section: Introductionmentioning
confidence: 99%